Environmental Temperature in Thermal Comfort Under Different Virtual Tourism Activity Intensities: Based on Microclimate Simulation Experiment - Wang, Linqiang; Wang, Jiahui; Huang, Xiaoting; Chi, Honglei (Frontiers in Neuroscience, 2022)
Although the lockdown and regulations to travel due to COVID-19 has restricted the space area for human activities, tourists can still use virtual devices and applications to travel. The study uses experimental and semi-structured interview methods, combed with microclimate simulation experiments and electrocardiogram to monitor physiological indicators, aiming to explore the thermal comfort and satisfaction of tourists under various virtual tourism activity intensities. The results showed that: (1) The thermal comfort of virtual tourism tourists has a significant correlation with the environmental temperature. (2) The thermal comfort of virtual tourism tourists is different under various activity intensities. The virtual tourism activity intensity moderates the relation between environmental temperature and tourists’ thermal comfort. (3) In the state of exercise (slow walking, fast walking), environmental temperature affected tourists’ physiological indicators. (4) Virtual tourism that integrates realistic visual, audio, and tactile sensations can improve tourists’ perception and satisfaction. The results provide a new perspective for the study of virtual tourism experience and thermal comfort. In addition, it provides theoretical and practical support for the development of virtual tourism scenes in the environmental temperature context.